BPJS SERVICE QUALITY AND PATIENT SATISFACTION: A MIXED-METHODS STUDY IN INDONESIAN PUBLIC HOSPITALS - Ferdy Rumambi; Peggy Mekel; Joni Kutu' Kampilong; Deisy Pangkey; Indah Kembuan; Gloria Mokat (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In Indonesia, the National Health Insurance (BPJS Kesehatan) has successfully facilitated access to healthcare, despite fluctuations in people's satisfaction with public hospitals. It is essential because services must be continually improved and maintained at a high standard to identify the most critical quality dimensions. We aim to investigate how these dimensions of service quality impact the level of satisfaction among BPJS patients in a qualitative setting. Our research approach was a combination method. We asked 188 BPJS patients questions regarding Tangibles, Reliability, Responsiveness, Assurance and Empathy. We used semi-structured interviews with 24 respondents to investigate their experience. Responsiveness (β = 0.312; p<0.001), assurance (β = 0.287; p<0.001) and empathy (β = 0.241; p<0.01) were significant predictors of satisfaction (R2 = 0.684; F = 162.37; p<0.001). The physical side was not very good, and its reliability was also subpar. Interviews revealed that participants were concerned with waiting times, the way the staff treated them and perceived a difference in the treatment of BPJS patients and non-BPJS patients. The attitudes and empathy of BPJS staff toward patients are the most influential factors in determining the level of satisfaction among BPJS patients. Hospitals should be taught how to communicate effectively, manage queues and appointments in real-time, and enhance service quality. Payers and managers at BPJS could include these items in contracts, compensate for performance, require total reporting on waiting and experience, and advocate for triage and staffing that minimize waiting times